THE NEED FOR A NEW DEFINITION OF SUSTAINABILITY - Shaharir b.M.Z.; Alinor M.b.A.K. (Journal of Indonesian Economy and Business (JIEB), 2013)
The present definition and scope of sustainability are reviewed by highlighting its various weaknesses including those that have been mentioned by Western scholars in development economics, ecological economics, environmental economics, and envirometrics. The emergence of a new field in the 1990’s, misleadingly named as eco-nomics, was to replace general economics. The presence of many forms of economics with new paradigms are purposely designed to improve development economics and at the same time to discuss and cope with the problems of sustainability. Our study on the nature and scope of sustainability was based on the history of the Malayonesian1 civilization and Islam, and practices of the present globalism. It has shown that not only is there a need to include an exhaustive environmental aspect (more than just the homo oeconomicus, flora and fauna) and a wider quantitative aspect (not just only statistics as well as other elements of mathematical science) but also to consider much more basic and important in the definition of sustainability. In this regard, we criticize the present mathematics used to measure sustainability. Other important aspects are the dimensions of knowledge and religion (with the emphasis on the importance of happiness) which we reclassify as two important components of culture which form our main focus of this paper. Examples of these new and classical elements of sustainability are partly based on our study inspired by relevant Malay inscriptions and manuscripts of direct and indirect effort of those in power and scholars of sustainability during the pre-Islamic and Islamic era of the Malayonesian civilization. In other words, our new definition of sustainability is proposed in order to improve the present definition and therefore involves the issue of interaction between beings, cultures and religions, together with a comprehensive value-laden mathematical science.